Effects of temperature on mechanical properties and impact resistance of carbon fiber/bismaleimide resin composites - Xinying Zhu; Shikai Yin; Lulu Liu; Wenzhao Yi; Gang Luo; Zhenhua Zhao; Wei Chen (Journal of Materials Research and Technology)
Bismaleimide (BMI) resin, a thermosetting material with superior heat resistance, mechanical strength, and environmental stability, is widely used in aerospace applications, especially in the military aircraft and turbofan engine characterized by high temperatures. While research has extensively covered the mechanical behavior of epoxy and thermoplastic composites, the effect of temperature on the BMI-based composites remains underexplored, especially within its service temperature range. Thus, a systematic study of the effects of temperature on mechanical properties and damage patterns of carbon fiber/bismaleimide resin composites was carried out through various experiments, ranging from quasi-static to dynamic and impact resistance. The test results of mechanical response curves, visual analysis, scanning electron microscopy, ultrasonic C-Scanning and X-ray tomography indicated that high temperatures reduce the interfacial properties, leading to diminished mechanical properties. The failure strain and modulus do not vary monotonically with temperature or strain rate, while the ballistic limit increases with temperature in general. These results provide valuable reference data and significant relevance of carbon fiber/bismaleimide resin composites in the aviation field.